Diagnostic Accuracy of Epithelial Membrane Antigen for Malignant Effusions: A Meta-Analysis. Issue 1 (2016) - Lin, Wentao; Liu, Xiaoxue; Cen, Ying
Background and Objectives: Body cavity fluid examination sometimes presents a diagnostic challenge in cytology practice. This meta-analysis was undertaken to comprehensively assess the diagnostic potential of epithelial membrane antigen (EMA) in malignant effusions. Materials and Methods: All relevant original articles about EMA in the diagnosis of malignant effusions published up to July 1, 2014 were retrieved. The overall sensitivity, specificity, positive and negative likelihood ratio, diagnostic odds ratio, and summary receiver operating characteristic (SROC) curve were pooled to evaluate the diagnostic value of EMA for malignant effusions using the Meta-Disc 1.4 and STATA 12.0 statistical software. Results: Eleven studies met the inclusion criteria for the meta-analysis and the summary estimates for EMA in the diagnosis of malignant effusions were as follows: sensitivity 0.9 (95% CI 0.83-0.87), specificity 0.87 (95% CI 0.96-0.99), positive likelihood ratio 5.8 (95% CI 15.59-36.37), negative likelihood ratio 0.15 (95% CI 0.07-0.20) and diagnostic odds ratio 52.63 (95% CI 20.91-132.49). The SROC curve indicated that the maximum joint sensitivity and specificity (Q-value) was 0.88; the area under the curve was 0.94. Conclusion: The present meta-analysis indicated that EMA may be a useful diagnostic tool with good sensitivity and specificity for differentiating malignant effusions from benign effusions.